The Role of Pencak Silat GASMI in Instilling Islamic Education Values in Surakarta: Peran Pencak Silat GASMI Dalam Menanamkan Nilai-Nilai Pendidikan Agama Islam Di Surakarta - Prasetiyo, Wahyu Agung; Salim, Hakimuddin (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Education is a key pillar in shaping a nation’s character, with Islamic Education playing a central role in cultivating moral and spiritual values. Specific Background: While pencak silat is widely recognized as a traditional martial art, its integration with Islamic educational values remains underexplored. Knowledge Gap: Existing studies focus mainly on pesantren-based silat practices, overlooking the role of urban-based organizations such as GASMI in Surakarta. Aims: This study aims to investigate the strategies, impacts, and challenges of internalizing Islamic values through pencak silat activities in GASMI Surakarta. Results: The findings indicate that GASMI fosters religious, ethical, and spiritual values—such as faith, discipline, humility, and worship—through structured methods including habituation, exemplary conduct, advice, and corrective sanctions. Novelty: Unlike prior studies, this research highlights how a community-based silat organization outside pesantren contexts can serve as a dynamic platform for character education rooted in Islamic teachings. Implications: The study offers a culturally resonant model for Islamic education that combines physical discipline with moral development, suggesting a blueprint for integrating local cultural assets into character education initiatives across diverse urban settings.Highlight : GASMI serves as a medium to instill Islamic values through martial arts training. Values are taught using habituation, exemplary behavior, advice, and disciplinary methods. The program fosters religious character and noble morals among youth in Surakarta. Keywords : Islamic Education Values, Pencak Silat, GASMI, Morality, Surakarta